Verbal Derivatives in V. Vynnychenko’s Prose: Word-building and Morphonological Aspect (Linguostylistic Studies, 2015)
In this article the linguistic organization of the writer’s language is considered, the specific of verbal derivatives in word-building and morphonological aspect through V. Vynnychenko’s prose is found out, the attempt to analyze the specific of appellative and proprietary vocabulary using in the writer’s prose is done, productive and non-productive derivational tools and morfonological models of verbal derivatives in V. Vynnychenko’s prose are pointed out; the specificity of appellative and proprietary vocabulary using in the writer’s prose is analyzed. The possible morfonological changes in word-building of verbal derivatives are foreseen; the peculiarities of morfonological transformations in V. Vynnychenko’s works are detected. It was established that truncation of the final verb morpheme is the total morfonological operation for all verbal derivatives which accompanies the emphasis position shift with the combination of alternations (mostly consonant). Key words: verbal derivative, formant, morphonological model, morphonological phenomena, appellative and proprietary vocabulary. References